Synchronized delivery of Er:YAG-laser-pulse energy during oscillations of vapor bubbles - Gregorčič, Peter (LAHA (Online ed.), 2014)
A laser system and a measuring method for the synchronized delivery of multiple Er:YAG - laser pulses during vapor - bubble oscillations are presented. We use a free - running Er:YAG laser, designed for laser dent istry. Our results reveal that for short Er:YAG laser pulses, spherical bubbles develop even if a flat - end fiber tip is used for delivery of the Er:YAG - laser pulses into water. We developed a method called a laser - beam - transmission probe for on - line monito ring of the bubbles' oscillations. By using this method combined with shadowgraphy, we show that the dissipation of the bubbles' energy during bubble oscillations can be efficiently balanced by the synchronized delivery of multiple Er:YAG - laser pulses. Our results show that the resonance effect is obtained when the second laser pulse is delivered at the end or slightly after the bubble's collapse. In this case the resonance effect increases the mechanical energy of the secondary oscillations. The presented PHAST (Photo Acoustic Synchronized Transients) method has great potential to open new opportunities for further development of modern laser - based dental treatments.
Keywords: endodontics; Er:YAG multiple pulses; laser - beam - transmission probe; laser dentistry; laserji v zobozdravstvu; laserska prepustnostna sonda; optodinamika; PHAST optodynamics; resonance effect; shadow photography; vapor bubble; večkratni Er:YAG bliski